Winter Ecology of Agricultural Birds: The Role of Crop Type in Habitat Occupation by the Eurasian Blackcap - Eyda Annier Moreno-Mosquera; Robby M. Drechsler; Juan S. Monrós (Sci, 2025)
Agriculture is an anthropic activity with a significant impact on the environment and biodiversity. Hence, the conservation and proper management of wildlife inhabiting agricultural areas is crucial to ensure both food production sustainability and biodiversity preservation. The presence and distribution of the Eurasian Blackcap (Sylvia atricapilla) was evaluated in different crops during winter and the influence of vegetation structure and altitude on its abundance was analyzed. It was hypothesized that the presence and abundance of the species would be influenced by vegetation structure and altitude. Sampling was conducted in 60 agricultural plots differentiating homogeneous and heterogeneous crops. Warblers were recorded by sight and hearing along 1 km transects. The effect of vegetation structure on the warbler abundance was analyzed by carrying out ANOVAs and Mann–Whitney tests. The Eurasian Blackcap was detected in 75% of the sampled plots. Significant differences in vegetation structure between occupied and unoccupied crops were not found; however, an effect of the altitude of the transects was observed, occupying mostly lower areas. The warbler abundance was not significantly affected by crop type nor sampling year. This study provides valuable information on the ecology and distribution of the Eurasian Blackcap in agricultural crops, enriching the knowledge on how to establish the sustainable management of croplands and ensure the conservation and proper management of the species in agricultural areas.